PENERJEMAHAN BUTIR BUDAYA DARI BAHASA INGGRIS KE BAHASA INDONESIA - Fuad Arif Fudiyartanto (Adabiyyāt: Jurnal Bahasa dan Sastra, 2012)
Culture specifics, i.e. the manifestation of culture in language, are unique and their translation is also quite complicated compared to other ordinary lexical items. The culture of the source language may not necessary have equivalence in the target language culture. However, it is believed that there are several alternative ways, or translation techniques, to solve the problem. The techniques such as choosing more common words, borrowing, translation by adaptation, or free translation by the culture of the target language (Indonesian), in addition to several other alternatives, can be used. The translation techniques for those culture specifics should be chosen on the basis of the text the translators are dealing with, and so they need to be careful in choosing the most appropriate one.